2011
DOI: 10.1111/j.1532-950x.2011.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sensory Field and Repeatability of the Cutaneous Trunci Muscle Reflex of the Dog

Abstract: Objective To describe the cutaneous trunci muscle (CTM) reflex in dogs. Study Design Prospective descriptive study. Animals Normal dogs (n = 155) and 10 dogs with thoracolumbar myelopathies. Methods The CTM reflex caudal border was assessed from the ilial crests moving cranially until a CTM contraction was elicited. The lateral borders were evaluated at 4 levels and the distance from the midline to the lateral border was expressed as a percentage of the trunk hemicircumference. The caudal border was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…The cutaneous trunci muscle reflex in normal dogs is present as far caudally as the skin overlying L5 or L6 vertebrae, as recently described in 153 of 155 normal dogs. 31 The recommendation in cases with trauma to the vertebral column is to image the entire spine to search for multiple lesions, all of which might not be clinically detectable. Five percent to 10% of cases with trauma to the vertebral column have multiple fractures or luxations.…”
Section: Umn Versus Lmnmentioning
confidence: 99%
“…The cutaneous trunci muscle reflex in normal dogs is present as far caudally as the skin overlying L5 or L6 vertebrae, as recently described in 153 of 155 normal dogs. 31 The recommendation in cases with trauma to the vertebral column is to image the entire spine to search for multiple lesions, all of which might not be clinically detectable. Five percent to 10% of cases with trauma to the vertebral column have multiple fractures or luxations.…”
Section: Umn Versus Lmnmentioning
confidence: 99%
“…The sensory stimulus induces a contraction of the CTM, producing a skin twitch. The caudal border of the CTM reflex lies at the level of the 6th lumbar vertebra (L6) in 97% of normal dogs . Thoracolumbar myelopathies affecting spinal cord segments T3 – L3 interrupt the ascending CTM reflex pathway, causing cranial movement of the caudal border, and this change in level of border is commonly used to localize spinal cord lesions.…”
mentioning
confidence: 99%
“…The literature suggests that the cutaneous trunci reflex may be absent in some healthy dogs and this could represent a limitation for using it clinically (De Lahunta and Glass ). However, studies in dogs concluded that the cutaneous trunci reflex could be reliably demonstrated in the vast majority (94 to 100%) of healthy dogs up to the vertebral level L6 (Fox , Muguet‐Chanoit and others , Muguet‐Chanoit and others ). The cutaneous trunci reflex was present in all dogs in this study, either cranial to the level of cut‐off or cranial to L6 in cases with no cut‐off.…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous trunci reflex is a polysynaptic reflex with intersegmental transmission of impulses. It is elicited by pinching the skin of the dorsal trunk between the second thoracic vertebra (T2) and the sixth to seventh lumbar vertebrae (L6 or L7) and observing a contraction of the cutaneous trunci muscles bilaterally (Holstege and others , Blight and others , Garosi , Muguet‐Chanoit and others ). Within the spinal cord segment corresponding to a particular dermatome, the sensory neurons synapse on long interneurons at the level of the dorsal grey column and the axons of these long interneurons enter the fasciculus proprius of the spinal cord bilaterally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation